Humanidades Digitales Miradas hacia la Edad Media - González, Déborah; Sabel, Helena Bermúdez (De Gruyter, 2018)
The contributions gathered in this volume show how digital technologies can be applied to Medieval Studies (Philology, Art, and History) in order to improve our understanding of medieval societies and cultures.